DEVELOPING EARLY CHILDHOOD COGNITIVE ABILITIES THROUGH NUMBER CARDS IN ADMAJARIA KINDERGARTEN - Rukayah Siti (Journal of Teaching and Education, 2025)
This study aims to describe and analyze the improvement of cognitive abilities of group B children, especially in the aspect of recognizing symbols and number concepts, through the implementation of Number Card media in Admajaria Kindergarten, Bojonegoro Regency. The main problem of this study is the low initial cognitive achievement, which is indicated by the pre-cycle completion percentage of 35.71% with an average value of 65.00. This study uses the Classroom Action Research (CAR) design model of Kemmis and McTaggart which was implemented in two cycles, with 14 Group B children (8 boys and 6 girls) as subjects. Data were collected through observation, tests, and documentation. The criteria for success of the action was set at 75% classical learning completion. The results of the study showed a significant and sustainable increase: in Cycle I, the completion percentage reached 64.28%; then in Cycle II, the completion percentage increased sharply to 85.71% with an average value of 80.00. These results have exceeded the set targets, proving that the use of Number Card media combined with active play strategies is effective and feasible for improving cognitive abilities, especially number recognition, in early childhood.